Cultural miscommunication faced by Faber Group Berhad when dealing with international subsidiaries / Syazwani Arbaiyah Mohd Shahir - Mohd Shahir, Syazwani Arbaiyah (2012)
This paper investigates and identifies the causes of cultural miscommunication faced by Faber Group Berhad when dealing with its international subsidiaries. It consists of investigating the cultural miscommunication that becomes a challenge for effective communication between Faber Group Berhad and its overseas branches particularly in India and Abu Dhabi. This research focuses on the three causes of cultural miscommunication faced by Faber when dealing with its international subsidiaries with respect to differences in values, communication styles and use of physical space. The researcher used interview as mean to collect data for the findings of this case study. The findings that the researcher found are that differences in values, physical use of space and communication styles do cause cultural miscommunication when Faber deal with its international subsidiaries.